Vitamin D deficiency, the urban epidemic: a cross-sectional study from Bhopal, India - Rao, P. V. Prakasa; Siddhartha, P. V.; Yeshwante, Prashant (International Journal Of Community Medicine And Public Health, 2020)
Background: Vitamin D is a fat-soluble vitamin involved in the regulation of calcium homeostasis and bone health. Vitamin D deficiency results in abnormalities in calcium, phosphorous, and bone metabolism. We undertook a study in our part of the country to register the incidence of the deficiency in our community, and compared Urban and Rural communities to understand the cause of the deficiency. Methods: This retrospective non-randomised cross-sectional study was carried out on asymptomatic patients undergoing blood tests due to various causes. 257 individuals consented to be part of the study and were divided into Urban (n=143) and Rural (n=114) groups. Incidence of Vitamin D deficiency, and various socio-behavioural parameters were compared. Results: The prevalence of Vitamin D deficiency was 91.6% in the Urban population and 66.5% in the rural population, which is statistically significant (p<0.00001). This was observed despite the urban group having statistically better nutritional status and lower tobacco consumption. Conclusions: Vitamin D deficiency is a widespread condition in community. Clinically diagnosed cases represent only the tip of the iceberg. This silent epidemic needs to be addressed with due attention and strong action.